Pengaruh Penerapan E-Voting Terhadap Tingkat Partisipasi Politik Masyarakat Pada Pemilihan Waliagari Batu Taba Kabupaten Agam Tahun 2019 - Novaldi, Rizki; Adnan, M Fachri (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
This research is motivated by the level of community participation in Nagari Batu Taba where there are still many levels of public apathy about politics, especially in general elections. In 2019, Nagari Batu Taba held a general election using e-voting which previously was still conventional (based on ballot paper). The purpose of the study was to analyze regardless of the effect of the application of e-voting on the level of community political participation in the Election of Walinagari Batu Taba, Agam Regency in 2019. The method used in this study is a quantitative method. Respondents in this study are people who are registered in the Permanent Voters List who use their voting rights in walinagari elections and are taken using the Simple Random Sampling technique. The results showed that the e-voting variable had a significant effect on conventional (paper-based) community political participation, which had an Adjust R Square value of 0.706 or 71% and the remaining 29% was based on other variables not examined in this study. In this case, the application of e-voting has a significant effect on the level of community political participation in the 2019 Election of Walinagari Batu Taba, Agam Regency.